2016
DOI: 10.1590/2359-3997000000208
|View full text |Cite
|
Sign up to set email alerts
|

Thyroxine increases Serca2 and Ryr2 gene expression in heart failure rats with euthyroid sick syndrome

Abstract: Objective: The current study was aimed at analyzing sarcoplasmic reticulum Ca 2+ ATPase (Serca2) and ryanodine receptor type 2 (Ryr2) gene expression in rats subjected to surgery that induced HF and were subsequently treated with T4 using physiological doses. Materials and methods: HF was induced in 18 male Wistar rats by clipping the ascending thoracic aorta to generate aortic stenosis (HFS group), while the control group (9-sham) underwent thoracotomy. After 21 weeks, the HFS group was subdivided into two su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(25 reference statements)
0
4
0
1
Order By: Relevance
“…TH has the potential to influence Ca 2+ levels in cardiomyocytes through multiple mechanisms, including regulating the expression of sarcoplasmic reticulum Ca 2+ -ATPase (SERCA2) and RyR2 [Ca 2+ cycling proteins; ( 149 )], and down-regulating Na + /Ca 2+ exchanger and phospholamban ( 150 – 153 ). Increased Ca 2+ influx and efflux rates also characterize hyperthyroidism in ventricular cells ( 154 ) most likely due to altered activation of sarcolemmal Ca 2+ channels and SERCA2 activity ( 148 , 155 ).…”
Section: Cardiac Electrical Remodeling Associated With Hyperthyroidism and Lt4 Treatmentmentioning
confidence: 99%
“…TH has the potential to influence Ca 2+ levels in cardiomyocytes through multiple mechanisms, including regulating the expression of sarcoplasmic reticulum Ca 2+ -ATPase (SERCA2) and RyR2 [Ca 2+ cycling proteins; ( 149 )], and down-regulating Na + /Ca 2+ exchanger and phospholamban ( 150 – 153 ). Increased Ca 2+ influx and efflux rates also characterize hyperthyroidism in ventricular cells ( 154 ) most likely due to altered activation of sarcolemmal Ca 2+ channels and SERCA2 activity ( 148 , 155 ).…”
Section: Cardiac Electrical Remodeling Associated With Hyperthyroidism and Lt4 Treatmentmentioning
confidence: 99%
“…The activity of the ATP2A2 pump is regulated in part by PLN which acts as a potent inhibitor in its phosphorylated state [52]. Contractile activity of the myocardium is upregulated by thyroid hormones which have been shown to signal an increase expression of RYR2 and ATP2A2 [53,54] and a decrease in PLN expression [55]. In the absence of thyroid hormone, thyroidectomized ovine fetuses showed a significant downregulation in cardiac ATP2A2 [35].…”
Section: Figure 5 Fetal Gene Expression Associated With Regulation Ofmentioning
confidence: 99%
“…Gene expression of RyR2 was markedly reduced under hypoxic conditions in our study, which is in line with reduced RyR2 gene expression observed in heart failure patients 36 and in rodent models of heart failure. 37 Despite the importance of RyR2 in intracellular calcium metabolism and the fact that the regulatory region of the RyR2 gene was characterized in 1996, 38 little information is available on the regulation of RyR2 gene expression in the literature. It has been demonstrated that severe food restriction down-regulates RyR2 gene expression 39 and that thyroxine treatment up-regulated RyR2 expression 37 in the heart, suggesting a link between RyR2 gene expression and the overall metabolic status of the cardiomyocyte.…”
Section: Discussionmentioning
confidence: 99%
“… 37 Despite the importance of RyR2 in intracellular calcium metabolism and the fact that the regulatory region of the RyR2 gene was characterized in 1996, 38 little information is available on the regulation of RyR2 gene expression in the literature. It has been demonstrated that severe food restriction down-regulates RyR2 gene expression 39 and that thyroxine treatment up-regulated RyR2 expression 37 in the heart, suggesting a link between RyR2 gene expression and the overall metabolic status of the cardiomyocyte. Interestingly, RyR2 mRNA levels as well as RyR2 function were found to be directly regulated by circadian rhythm proteins (e.g., clock protein) in the suprachiasmatic nucleus.…”
Section: Discussionmentioning
confidence: 99%